Analysis with Business Model Life Cycle Assessment for Innovation of a Circular Business Model A case study of rental products at events - Claesson, Albin; Skogum, Christoffer (My University, 2023)
Plastic waste in seas and oceans is growing and becoming a larger problem. As of 2022, it was estimated that there are 139 million tonnes of plastic waste in the Earth’s aquatic environments where it harms wildlife and ecosystems (OECD, 2022). Simultaneously as the plastic waste in the oceans increase, legislations, and regulations to mitigate the environmental problem of plastic waste are beginning to being implemented (European Parliament, Council of the European Union, 2019). The Swedish government has decided that by 2024, no disposable cups with more than 15% of plastic is allowed to be sold, as response to the European Parliament’s legislation (Swedish Government, 2021).With new business models appearing, a problem rises. Substituting old business models with new ones that uses multiple use products is only beneficial if the new business models are more environmentally sustainable than the old ones. Furthermore, there has been a problem when trying to assess the environmental performance of business models as conventional product LCA often is used for assessment but fails to capture the social and economic dimensions of business model (Böckin et al., 2022). As conventional product LCA assesses a physical entity, the product as a unit and not the entire business model. The aim of this project is to understand the environmental performance of the Light My Fires rental business model for events. Furthermore, the study aims to enable business model innovation by running a sensitivity analysis that shows how the environmental impacts changes due to changes of the business model such as the return rate, rental price, loss fee, storage location and material and manufacturing cost. Lastly, the intended outcome of the project is to answer what the environmental performance of the studied business model is, what environmental hotspots there are, and suggest courses of action to maintain profit of the company while minimising the environmental impact. The functional unit of the study was desired profit level during an event season for Light My Fire.The GWP per f.u. was: 0,037 kg CO2 eq/f.u. It was found that the largest hotspots for all impact categories: Global warming potential100, Marine aquatic ecotoxicity, Acidification, Terrestrial ecotoxicity, Fresh water aquatic toxicity, Human toxicity, Abiotic depletion, Ozone layer depletion, Photochemical oxidation, Eutrophication, Abiotic depletion (fossil fuels) analysed, were the production for making up for losses depended on the return rate, the transports between Västervik, Gothenburg and Malmö, and the production of polypropylene. Interestingly, it was revealed that the return stations effect on the environmental performance of the business model was of great significance. From the sensitivity analysis it was found that the most significant change in environmental impact with a high possibility of implementing was to increase the return rate after each event. By increasing the return rate to 85% the business model would lower the kg CO2 eq/f.u. with 23% as production of new products were decreased and ultimately decreasing the need for extra transports. Furthermore, it showed that moving the storage facility to the same city as the event reduced the contribution to total emissions from transports with 8%. Further, combining the increase of return rate, with the change of storage facility entails a 32% reduction in kg CO2 eq/f.u. Studies have shown that sustainable business models are considered to reduce impacts to environment and society (Bocken et al., 2014). However, this study showed that marketing business models as sustainable without analysing its entirety could have implications in the form of unforeseen impacts. Subsequently, there are possibilities to improve sustainable business models with business innovation using the BMLCA method. Ultimately, the BMLCA worked as a tool for analysing and evaluating the environmental performance of a rental business model used at events with a timeless functional unit. The rental case differed from previous conducted studies since the case was conducted at a real event which has not been done previously, however, the method presented in this study could be successfully modified and subsequently applied to the rental business model at events.
Keywords: BMLCA; business model innovation; environmental impacts of business models